Sosialisasi Tanaman Herbal Dan Pembutan Jahe Instan Di Kelurahan Sambuli Kecamatan Nambo - Ari, Ari Sartinah; Nur Illiyyin Akib; Halik, Halik; Rifa’atul Mahmudah; Muhammad Mahfudz Nur (Jurnal Pengabdian UntukMu NegeRI, 2022)
Nambo District is one of the coastal tourist destinations for the Kendari city community and its surroundings. As a tourist place, many mobilities of residents from outside enter the Nambo District area, making it vulnerable to the spread of the COVID-19 outbreak. In addition, there is still a lack of awareness of some people to implement the Healthy Living Community Movement, including the lack of knowledge of some people in utilizing and processing nutritious herbal plants into herbal medicines that can be used as traditional medicines in maintaining and improving health during a pandemic. The solution to this problem is counseling/socialization and education about using and strengthening efficacious herbal plants and making packaged herbal medicine (instant ginger), which are practical steps in maintaining and improving health during a pandemic and can have sold/economic value.